Marital Vows in the Hindu Marriage System: A Feminist Perspective (The Harvest, 2026)
This paper examines the Hindu marriage ceremony (Vivaha Sanskara). It argues that the traditional Sanskrit vows create a partnership of equals, rather than a system where men control women. By closely studying the “Seven Conditions of the Bride” (Kanyake Sat Vachan) and the “Seven Steps” (Saptapadi) dialogue found in the Vivaha-Sanskar-Paddhati (Gita Press), this research interprets the ritual words using Simone de Beauvoir’s feminist ideas. The analysis shows that the bride actively bargains for her rights. She explicitly demands control over household money (madadhīnaṁ), the freedom to keep her friends (sakhīparivṛtā), and a role in business and religion. The paper argues that these conditions meet Beauvoir’s definition of “real love” because they build a relationship based on friendship. The groom even calls the wife a “Friend” (Sakha) rather than a servant. Finally, the study concludes that these religious texts provide a strong argument for gender equality, challenging the common social view that a wife is inferior to her husband.